Sebaran Kanker di Indonesia, Riset Kesehatan Dasar 2007 - MAKASSARI DEWI (Indonesian Journal of Cancer, 2017)
ABSTRACTCancer is one of the leading causes of death in the world. It takes an evidence-based strategy to address the increasing incidence of cancer in the world. To control the increase of cancer in Indonesia required control strategies of the key riskfactors associated with the incidence of cancer. Currently the data on the distribution of cancer in Indonesia is still limited. Key risk factors for cancer can be known from the existing types of cancer. By knowing the distribution of cancerthat is expected to become a factor in the prevention of cancer in Indonesia. The purpose of this paper is to describe the distribution of cancer in Indonesia by the community in 2007. The data used is data survey of basic health research(Riskesdas) 2007. Design this study was a descriptive cross-sectional. The analysis showed that from 768 635 respondents there were 4647 (0.6%) respondents who had cancer. Central Java province was the province with the highest number of cancer patients (23.6%). Cervical and ovarian cancer as well as breast cancer were the most commonly found as many as 927 (20%) of respondents to cervical and ovarian cancer, and as many as 746 (16%) of respondents had breast cancer. Cervical and ovarian cancer were most commonly found in adults, with the status ofmarried, live in urban areas and have low education status. Breast cancer was most common in women aged adult, married status, living in urban, low educational status and low economic status.ABSTRAKKanker merupakan salah satu penyebab kematian utama di dunia. Dibutuhkan strategi berbasis bukti untuk mengatasi meningkatnya kejadian kanker di dunia. Untuk mengontrol peningkatan kanker di Indonesia diperlukan strategipengendalian faktor risiko kunci yang berhubungan dengan kejadian kanker. Saat ini, data tentang sebaran kanker di Indonesia masih terbatas. Faktor risiko kunci kanker dapat diketahui dari jenis kanker yang ada. Dengan mengetahuisebaran kanker yang ada diharapkan dapat menjadi salah satu acuan dalam penanggulangan kanker di Indonesia. Tujuan dari tulisan ini adalah untuk menggambarkan sebaran kanker di Indonesia berdasarkan komunitas pada tahun2007. Data yang digunakan adalah data surveI Riset Kesehatan Dasar (Riskesdas) 2007. Desain studi ini adalah deskriptif cross-sectional. Hasil analisis menunjukkan bahwa dari 768.635 responden, 4.647 (0,6%) responden di antaranya menderita kanker. Jawa Tengah merupakan provinsi dengan jumlah penderita kanker tertinggi (23,6%). Kanker serviks uteri dan ovarium serta kanker payudara merupakan jenis kanker yang paling banyak ditemukan, yaitu 927 (20%) responden untuk kanker serviks uteri dan ovarium serta 746 (16%) responden kanker payudara. Kanker serviks uteri dan ovarium paling banyak ditemukan pada usia dewasa, dengan status menikah, hidup di perkotaan, dan memiliki status pendidikan rendah. Kanker payudara paling banyak ditemukan pada wanita usia dewasa, status menikah, tinggal di perkotaan, status pendidikan rendah, dan status ekonomi rendah.